Phenomenology Causes of the Low Application of Community-Based Total in Coastal Area, Konawe Island Regency - Anil Musmina, Nila; Azizi Jayadipraja, Erwin; Umi Nurlila, Ratna (Waluya The International Science of Health Journal, 2023)
Introduction: Community-based total sanitation is a strategy for involving the community in sanitation programs that are carried out to change sustainable hygienic and sanitary behavior. The coastal area of Konawe Kepulauan Regency ranks the 2nd lowest in the implementation of Community-based total sanitation. The purpose of this study was to determine the cause of the low community-based total sanitation Stop Open Defecation and Management of Household Waste in the Coastal Area of Konawe Islands Regency. Method: This type of research uses qualitative research, a phenomenological approach. Informants consist of key informants as many as 5 people, regular informants 7 people, and people residing in the area of Langara and Lansilowo Health Center. Snowball sampling technique and data analysis using data reduction, data display, and data conclusion techniques. Result: The results showed thatthere are still many people who have not implemented stop defecation due to a lack of knowledge, housing conditions in coastal areas, lack of latrines, habituation, and the economy. The community does not dispose of waste in its place due to several factors, namely the absence of a temporary disposal site and final disposal site. Conclusion: The phenomenon that causes people not to apply community-based total sanitation in the Coastal Area of Konawe Islands Regency is due to a lack of community knowledge, economic factors, lack of facilities or infrastructure, and also a habitual factor so that they have not implemented Community-based total sanitation on the coast of Konawe Islands Regency